Pneumococcal antigen in lobar pneumonia. - Tugwell, P (1975)
This paper describes the value in diagnosis and the clinical implications of the detection of pneumococcal antigen in patients with lobar pneumonia. Ninety-eight patients with lobar pneumonia were investigated. Pneumococcal antigen was detected by counter-current immunoelectrophoresis in the sputum of 79% of patients with purulent sputum, in the serum of 29% of the patients, and in the urine of 54% of the patients. The diagnostic value of counter-current immunoelectrophoresis was not affected by prior antibiotic therapy. Patients with antigenaemia had a higher incidence of complications than those without as shown by an association between antigenaemia and jaundice, diarrhoea, and persistent pyrexia. Antigen persisted in the circulation for at least seven days in half the patients studied, possibly indicating the development of immunological tolerance to the polysaccharide antigen.